2015
DOI: 10.21101/cejph.a4081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exergames on Balance, Functional Mobility, and Quality of Life of Geriatrics Versus Home Exercise Programme: Randomized Controlled Study

Abstract: SUMMARY Aim:To compare the effects of exergames (EGs) using the Xbox KinectTM device and home exercise (HE) on balance, functional mobility, and quality of life of individuals aged 65 years or older.Method: One hundred participants who met the inclusion criteria were randomized to the EG or HE group. The EG group took part in a 6-week programme using the Xbox360Kinect TM device, and the HE group took part in a 6-week balance exercise programme at home 5 days a week. The Berg Balance Scale (BBS) was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 12 publications
(22 reference statements)
4
44
0
6
Order By: Relevance
“…The fact that the iTUG improved after training with the BioRescue, is in line with the results of Rendon et al25 ) who showed that the eight feet up and go improved significantly after six weeks of training with the Wii Fit. Further, Karaha et al demonstrated a significant effect on balance, functional walking and quality of life after 6 weeks of virtual reality gaming using the Xbox KinectTM26 ) . Results on the tinetti-POMA test did not improve in contrast to earlier published research on cognitive-motor dual task training using the Wii Fit.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the iTUG improved after training with the BioRescue, is in line with the results of Rendon et al25 ) who showed that the eight feet up and go improved significantly after six weeks of training with the Wii Fit. Further, Karaha et al demonstrated a significant effect on balance, functional walking and quality of life after 6 weeks of virtual reality gaming using the Xbox KinectTM26 ) . Results on the tinetti-POMA test did not improve in contrast to earlier published research on cognitive-motor dual task training using the Wii Fit.…”
Section: Discussionmentioning
confidence: 99%
“…The association between general health and video games has received extensive attention in the academic literature [ 20 , 21 , 22 ], whereas the association between esports participation and general health has not [ 7 ]. Often in video gaming studies, general health is measured through a combination of physical, mental, and/or social health factors [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Videogame-based exercise has been shown to improve balance, and individuals are more motivated to exercise if they find the games to be challenging and enjoyable (Lamoth et al, 2011). Karahan et al (2015) concluded that IVGs can be considered a safe and entertaining alternative for older adults and may have positive effects on balance, functional walking, and quality of life. This study demonstrated the value of occupational therapy intervention in a virtual environment in the client factors and performance skills to contribute to the participant's health and well-being (AOTA, 2014).…”
Section: Thought It Was Funmentioning
confidence: 99%
“…IVGs are potential tools for occupational therapy practitioners to improve balance and functional mobility and to increase engagement in meaningful activities in older adults (Karahan et al, 2015;Skjaeret et al, 2015). IVGs are an attractive and interactive way to motivate individuals to engage in physical activity by combining both cognitive and motor skills focusing on the outcome of movements in the game and not the movement itself (Lamoth, Caljouw, & Postema, 2011).…”
mentioning
confidence: 99%